Updated survey on interventional electrophysiology: 5-Year follow-up of infrastructure, procedures, and training positions in Germany - Eckardt, Lars; Thomas, Dierk (JACC Clinical electrophysiology, 2018)
Objectives - This study provides an update and comparison to a 2010 nationwide survey on cardiac electrophysiology (EP), types and numbers of interventional electrophysiological procedures, and training opportunities in 2015. - Background - In 2010, German cardiology centers performing interventional EP were identified and contacted to provide a survey on cardiac EP. - Methods - German cardiology centers performing interventional EP in 2015 were identified from quality reports and contacted to repeat the 2010 questionnaire. - Results - A majority of 131 centers (57%) responded. EP (ablation procedures and device therapy) was mainly part of a cardiology department (89%) and only independent (with its own budget) in 11%. The proportion of female physicians in EP training increased from 26% in 2010 to 38% in 2015. In total, 49,356 catheter ablations (i.e., 81% of reported ablations in 2015) were performed by the responding centers, resulting in a 44% increase compared with 2010 (the median number increased from 180 to 297 per center). Atrial fibrillation (AF) was the most common arrhythmia interventionally treated (47%). At 66% of the centers, (at least) 2 physicians were present during most catheter ablations. A minimum of 50 (75) AF ablations were performed at 80% (70%) of the centers. Pulmonary vein isolation with radiofrequency point-by-point ablation (62%) and cryoablation (33%) were the preferred ablation strategies. About one-third of centers reported surgical AF ablations, with 11 centers (8%) performing stand-alone surgical AF ablations. Only one-third of the responding 131 centers fulfilled all requirements for training center accreditation. - Conclusions - Comparing 2010 with 2015, an increasing number of EP centers and procedures in Germany are registered. In 2015, almost every second ablation was for therapy for AF. Thus, an increasing demand for catheter ablation is likely, but training opportunities are still limited, and most centers do not fulfil recommended requirements for ablation centers.
Gesehen am 12.07.2019